Numerical and experimental investigations on the physical characteristics of supersonic steam jet induced hydrodynamic instabilities. Issue 2 (7th January 2016) - Khan, Afrasyab; Sanaullah, Khairuddin; Takriff, M. Sobri; Zen, Hushairi; Rigit, Andrew Ragai Henry; Shah, Ajmal; Chughtai, Imran Rafiq
Abstract: Hydrodynamic instabilities play a silent lethal role for the systems involving steam as one of its working fluid. They reduce the fatigue life of the pipes by exerting stresses at their walls. These instabilities created at the interface between steam and water and propagated towards the walls of the confinement. In the current research, three physical characteristics of these hydrodynamic instabilities have been discussed using Computational Fluid Dynamic (CFD) as well as experimental approaches. These characteristics include their spatial prevalence on the length scale, amplitude, and the number of their occurrences. All of these characteristics have been predicted at specific hydrodynamic conditions in terms of temperature fluctuations. It has been observed that these characteristics are exhibited by the hydrodynamic instabilities in a random and non‐deterministic manner. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.